Three Decades of Butterfly–Plant Interaction Turnover Explained by Climate and Species Loss - Pau Colom; Constantí Stefanescu; Jordi Corbera; Amparo Lázaro (Ecology Letters, 2026)
Understanding the mechanisms behind interaction turnover over long‐term periods is essential to predict how ecological networks respond to global change. We used a high‐resolution dataset of butterfly–plant interactions spanning 13–29 years in seven Mediterranean communities to assess how climate fluctuations and community shifts shape interaction turnover and its components—species turnover and rewiring. Rewiring contributed the most to interaction turnover, but its relative importance declined over time as species loss reduced the pool of shared partners between years. Consequently, species turnover became increasingly influential, even though communities shifted toward butterfly species with generalist traits that promote rewiring. Nevertheless, rewiring intensified in years with stronger temperature fluctuations, when populations experienced greater shifts in phenology and abundance and were more likely to rewire. In the context of biodiversity loss, species turnover increasingly governs interaction dynamics, while the short‐term flexibility provided by rewiring may collapse as communities become impoverished.

The Interplay of Climate Change, Urbanisation, and Species Traits Shapes European Butterfly Population Trends - Pau Colom; Ashley Tejeda; Simona Bonelli; Benoît Fontaine; Mikko Kuussaari; Dirk Maes; Xavier Mestdagh; Miguel L. Munguira; Martin Musche; Lars B. Pettersson; David Roy; Johannes Rüdisser; et al. (Global Ecology and Biogeography, 2026)
Aim To examine how butterfly population trends respond to climate change and urbanisation at a continental scale, and whether responses differ between urban and rural environments. Location 869 sites across 12 European countries, spanning six bioclimatic zones. Time Period 1976–2021. Major Taxa Studied Butterflies (Lepidoptera). Methods We analysed long‐term monitoring data from > 8400 populations of 145 species representing a wide range of ecological and life‐history traits. Population trends were modelled in relation to climate variables (temperature, precipitation and aridity), urbanisation (built‐up surface), and their interactions with urban context (urban vs. rural) and species traits (trophic specialisation, body size, reproductive rate and thermal adaptation). Results Climate warming and aridification were consistently linked to population declines in both rural and urban contexts, while precipitation effects varied by location and species. Urbanisation alone did not predict trends, but the urban–rural context strongly modulated species' responses to warming, indicating potential synergies between climate change and urbanisation. The stronger impact of warming in urban populations likely reflects elevated baseline temperatures and reduced habitat suitability and connectivity in urban landscapes, limiting thermal buffering. Species with colder thermal niches and lower reproductive rates were most vulnerable to warming, as warming exceeds the thermal optima of cold‐adapted species and lower reproductive rates limit their capacity to buffer climate‐driven population declines. Under aridification, which can reduce host‐plant availability, trophic specialists declined more in urban areas, whereas generalists unexpectedly declined more in rural sites, suggesting context‐dependent constraints under increasing water limitation. Main Conclusions Our findings highlight the complex interplay between climate change, urban context, and species traits in driving population dynamics. Importantly, our results suggest that urbanisation generally amplifies the negative impact of climate change on insect population trends.

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Effects of food availability on butterfly diversity and network specialization across altitudinal levels in a Mediterranean landscape - Jesús Sánchez-Dávila; Anna Traveset; Pau Colom (Biodiversity and Conservation, 2024)

Long-term effects of abandonment and restoration of Mediterranean meadows on butterfly-plant interactions - Pau Colom; Anna Traveset; Constantí Stefanescu (Journal of Insect Conservation, 2021)

Long-term monitoring of Menorcan butterfly populations reveals widespread insular biogeographical patterns and negative trends - Pau Colom; David Carreras; Constantí Stefanescu (Biodiversity and Conservation, 2019)